Development Planning Of Office Rental Building 5 Floors In Semarang City - Dika Dwirahmanda; Talitha Zhafira; Yuni Winarsih; Ngudi Hari Crista (Program Studi Sarjana Teknik Sipil Universitas Internasional Batam, 2024)
Since the COVID-19 pandemic in March 2020, the economy of Semarang has grown. The demand for office space has increased due to business expansion, resulting in high land prices due to government restrictions on development. Renting office space has become an effective solution by utilizing space vertically and providing adequate facilities. In the construction of tall buildings, mature structural planning is necessary to ensure stability and compliance with the latest SNI standards. Structural analysis follows the requirements of SNI (2847-2019) for structural concrete and SNI (1726-2019) for earthquake resistance planning. The research method involves primary data such as building technical drawings, soil data, and earthquake data, which are then analyzed using ETABS V.18 software. The analysis results show a maximum story displacement of 68.838 mm in the X direction and 83.941 mm in the Y direction, with a permissible structural displacement of 90 mm. The maximum story drift ratio in the X and Y directions is 0.009 mm and 0.011 mm, respectively, with a permissible structural drift ratio of 0.0909 mm. The largest torsion irregularity in the X and Y directions is 1.0813 and 1.1781, respectively, which are both below the permissible torsion irregularity value of 1.4. It can be concluded that the building is categorized as safe as it does not exceed the limits of displacement and torsion.